Quotes for Female and Male: Are They Different? - Wani Kesuma; Havid Ardi (English Language and Literature, 2022)
Quotes are written for various types. There are quotes motivation, advice, love, religion, humor and trend. Then, quotes intended for female, male and female-male. This study analysis the transitivity in Instagram quotes made by mr. amarisoul. This study aims to find out the differences of transitivity between quotes for female, male and female-male in Instagram quotes made by mr.amarisoul. This study used the theory by Halliday & Matthiessen, Systemic Functional Linguistics as Ideational Function. There are three elements of transitivity, those are processes, participants and circumstances. The data in this study were clauses in quotes. The source of the data is quotes from account mr.amarisoul in Instagram from September to December 2021. There are 306 processes that found in 46 quotes. The dominant process that appears in quotes for female is relation process 37%. The dominant process in quotes for male is mental process with 30.3%. Then, the dominant process in quotes for female-male is material process with 54.5%. The research concludes that relation process is the most dominant process that commonly appears in quotes. The dominant participants of relation process are carrier, attribute, token and value.  Based on this research, the researcher found that the quotes intended for female and male have different process. Quotes female use relation process and quotes male use mental process. Quotes have implications that can encourage and inspire people to take actions that make change in their lives.